A new surgical technique to facilitate osteochondral autograft transfer in osteochondral defects of the capitellum: a case report - BİLSEL, İSMAIL KEREM; Bilsel, Kerem; Demirhan, Mehmet; Atalar, Ata Can; Akkaya, Semih (My University, 2010)
A 17-year-old boy who was engaged in amateur weightlifting and body building presented with complaints of right elbow pain and limitation in elbow range of motion. Plain x-rays and magnetic resonance imaging showed an osteochondral defect in the medial third of the capitellum. At surgery, as a new technique, the lateral collateral ligament was detached from the humeral attachment to provide access to the capitellum with a clear and perpendicular exposure. Following removal of loose fragments within the joint, an osteochondral graft harvested from the lateral femoral condyle was implanted to the defect area of the capitellum. Postoperative radiologic controls showed that the defect was entirely filled by the graft with appropriate graft height. On follow-up examination at 12 months, the patient did not have any complaint about his elbow, and had no limitation of movement compared to the left elbow. Magnetic resonance imaging showed that the graft was successfully adapted to the recipient site without any sign of loosening. At final follow-up 40 months after surgery, the surface of the articular cartilage appeared normal. The range of elbow motion was preserved and the patient had no restriction in daily and sports activities. Considering technical difficulties posed by the narrow and complex structure of the elbow joint, this new technique involving detachment of the lateral collateral ligament facilitates perpendicular implantation of the graft. In our opinion, utilization of this new technique will improve functional and radiological results of osteochondral autograft transfer.